1972
DOI: 10.1002/pssa.2210110122
|View full text |Cite
|
Sign up to set email alerts
|

The effect of growth rate on the defect structure and dielectric properties of tgs single crystals

Abstract: The defect structure of TGS single crystals grown at constant temperature above TC, each at different constant supersaturation, is investigated by ultramicroscopy and Lang X‐ray topography. It is found that the defect density decreases with decreasing growth rate even at rates lower then 1 mm/d. The decreasing volume defect and dislocation densities are followed by an increase of maximum permittivity εmax, a decrease of coercive field Ec and a slight increase of the temperature of the phase transition TC. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Crystal growth conditions of pure crystal were intensively studied [2][3][4][5]. Synthesis and purification of the basic material, by fractional recrystallization, peculiar growth kinetic of the crystal and the influence of impurities were previously studied [4].…”
Section: Introductionmentioning
confidence: 99%
“…Crystal growth conditions of pure crystal were intensively studied [2][3][4][5]. Synthesis and purification of the basic material, by fractional recrystallization, peculiar growth kinetic of the crystal and the influence of impurities were previously studied [4].…”
Section: Introductionmentioning
confidence: 99%
“…Triglycine sulphate crystals (TGS) with large applications as a pyroelectric material was intensively studied in relation with its growing conditions (MARECEK, NOVAK;TSEDRIK et al 1975TSEDRIK et al , 1976MALEK et al). However, growth kinetics at large supersaturations were not performed, except (001) type face (REISS et al).…”
Section: Introductionmentioning
confidence: 99%
“…These defects could be induced by high supersaturated solution growth. [12][13][14] In this study, we first examined the crystal defect generation process via in situ observation and showed that slow crystal growth rate can reduce the crystal defects, such as hopper crystals and solution inclusions. Next, we employed the seeding method and the slow cooling method to realize slower growth and achieve better crystallinity of form II crystals.…”
mentioning
confidence: 99%